Culture possibility of scheilbeid catfish using formulated feed in natural pond (Journal of the Bangladesh Agricultural University, 2010)
A research study was conducted to investigate the culture possibility of fresh water catfish Pangasius pangasius with formulated feed in natural ponds. The stocking density was chosen as 8000 fry/ha with an initial weight of 42.57±2.51 g. The formulated feed contained 45% fishmeal, 30% mustard oil cake, 15% wheat bran and 10% rice bran to supply 40.48% protein in feed. The growth of Pangasius pangasius in terms of net weight gain was found as 266.49g, which was statistically significant (p